Counting sheep : reflections and observations of a Swedish shepherd - Lindén, Axel, 1972- (Atria Books, 2018)
When Axel Lindén leaves his literary life in the city for the farm he unexpectedly inherits<U+2014>along with the ever-escaping flock of sheep that comes with it<U+2014>he has a fairly naïve notion of what farm life will be: pure drudgery. But as time passes and Axel slowly settles into the rhythms of the farm and shepherding, his naiveté fades away and is gradually replaced with a new appreciation of the spiritual and emotional value of manual labor, caring for other living things, and staying connected to the earth. Capturing his observations and thoughts in short diary entries, Counting Sheep is a meditative and irresistibly delightful book that delves into the small wonders of our world and celebrates pastoral life, demonstrating that it<U+2019>s often the little things in life that mean the most.